Washing oiled sea otters - David A. Jessup; Laura C. Yeates; Sharon Toy‐Choutka; David Casper; Michael J. Murray; Michael H. Ziccardi (Wildlife Society Bulletin)
Abstract The 1989 Exxon Valdez oil spill resulted in the death of 3,000–6,000 sea otters (Enhydra lutris) from exposure to Alaska North Slope crude oil, and the cleaning and rehabilitation of hundreds. The washing and care methods developed during that experience provided standard protocols for treatment of oiled sea otters, largely still in use 20 years later. From 2004 to 2008 at the Marine Wildlife Veterinary Care and Research Center (Santa Cruz, CA, USA), we experimentally manipulated water type (salt–fresh) and temperature, and we monitored otter physiology, behavior, and thermal properties to evaluate recovery from washing in the absence of oil. We also dipped otters in canola oil, and were able to wash one otter naturally oiled with Monterey formation crude oil, using the same methods. Providing soft freshwater in recovery pools reduced recovery time substantially. Warming the freshwater appeared to offer additional benefits in some cases. Infrared thermography and subcutaneous temperature‐sensitive passive integrated transponder tags were 2 new technologies that enhanced this research. The improved washing and care methods developed have the potential to reduce the time required for recovery of water repellency of sea otter pelage. © 2012 The Wildlife Society.